Curettage and cryosurgery for enchondroma and atypical cartilaginous tumors of the long bones: Oncological results of a large series. Issue 8 (13th March 2021) - Deckers, Claudia; de Leijer, Esther M.; Flucke, Uta; de Rooy, Jacky W. J.; Schreuder, H. W. Bart; Dierselhuis, Edwin F.; van der Geest, Ingrid C. M.
Abstract: Background and Objectives: Intralesional surgical treatment is the preferred therapy for atypical cartilaginous tumors (ACTs) of the long bones in many institutions. However, the literature is still controversial regarding intralesional treatment versus wide resection. Due to the relative rarity of these tumors, studies reporting on the results of intralesional treatment are often small sample studies. Methods: We retrospectively analyzed the oncological results of 55 enchondromas, 119 ACTs, and 5 chondrosarcomas grade 2 (CS2) treated with curettage and cryosurgery between the years 2004 and 2017 at our institution. The median follow‐up period was 53 months (range, 24–169 months). Results: In total, seven cases (three ACT, four CS2) recurred. Residual tumor was detected in 20 cases. Three cases underwent secondary curettage and cryosurgery due to local recurrence. Four cases underwent wide resection and reconstruction due to local recurrence with aggressive imaging characteristics. In total, 20 postoperative complications were seen. Conclusion: Curettage and cryosurgery for enchondroma and ACT show very good oncological results with a low recurrence rate and acceptable complication rate. Curettage and cryosurgery is reliable as a surgical treatment for enchondroma and ACT. Further research should define the criteria for determining which specific cartilaginous tumors necessitate surgical treatment. Highlights: Curettage and cryosurgery is recommended as surgical treatment of enchondroma and atypical cartilaginous tumors (ACT) located in the long bones. Curettage and cryosurgery for enchondroma and ACT shows very good oncological results with a low recurrence rate and acceptable complication rate.